Effect of a daily outdoor access on milk quality and behavior of Italian Simmental dairy cows - Bailoni, L.; Arango, S.; Guzzo, N.; Curró, S.; Amalfitano, N.; Bianco, E.; Simonetti, E.; Rainis, S.; Sartori, C. (Frontiers in Veterinary Science, 2025)
This study aimed at assessing the effect of a two and a four-hour daily outdoor access on milk quality and behavior of dairy cows. Six Italian Simmental lactating cows housed in a free-stall were paired and subjected to the treatments: no outdoor access (CTR), two-hour daily outdoor access (U2; 11:30 a.m. to 1:30 p.m.), and four-hour daily outdoor access (U4) divided into a morning (9:00 to 11:00 a.m.) and an afternoon (2:00 to 4:00 p.m.) exit. Using a crossover design, each pair of cows was subjected to each treatment for 2 weeks, then switched twice, until the completion of 6 weeks of evaluation. Variations in milk parameters were determined across the treatments (CTR, U2, U4). Outside behaviors were assessed during the two-hour stay in the paddock, whereas inside behaviors were considered in the same timeslots plus an additional timeslot (4:00 p.m.–6:00 p.m.) in which the three treatments were inside the stall. Milk yield, composition and cheese-making traits were not affected by the outdoor access, but the coagulation properties were suggestively significant (p < 0.1). The longest rennet coagulation time (RCT, 21.31 min) and the lowest curd firmness (a30, 26.66 mm) were shown in U2. During the time spent outdoors, cows significantly increased their time standing resting (60.91 vs. 23.96 min; p < 0.001) and self grooming (6.58 vs. 2.96 min, p < 0.001); whereas, behaviors such as running, recumbency, drinking, eating, exploring and positive and negative interaction were reduced. When outdoors, cows spent most of their time standing resting (60.91 min), ruminating (11.10 min) and walking (10.62 min). Indoors, they spent more of their time eating (35.02 min), standing resting (23.96 min) and ruminating (13.84 min). Behaviors that were significantly affected by the treatment within each timeslot were: running, standing, resting, ruminating and eating. In conclusion, offering lactating dairy cows a four-hour daily outdoor access split into 2 h in the morning and 2 h in the afternoon appears to be beneficial because it increased the time spent standing resting outdoors which may indicate a calm state for the animals, while maintaining milk quality at a level comparable to that of full indoor management.